Les zones urbaines criminelles - Cusson, Maurice (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1989)
The study of criminal areas has been a longstanding tradition in sociology and criminology. It had its hour of glory during the publication of the works of Shaw and McKay of the University of Chicago. In this article — which is an account of the studies on the concentration of criminals in urban areas — we show that, since the XIXth century, large metropolises have relatively stable sectors where the social control is weak and opportunities to commit crimes are numerous. Networks of juvenile delinquents and adult criminals develop in these areas, fostering the transmission of criminal solutions. The article contains a description of the process that leads to the emergence of a crime zone. It ends with a critique on ecological studies and by an appeal for the study of conflicts within these criminal networks.